2019
DOI: 10.1080/10934529.2019.1605779
|View full text |Cite
|
Sign up to set email alerts
|

Levels of tin and organotin compounds in human urine samples from Iowa, United States

Abstract: Exposure to tin in the general US population is near ubiquitous, as determined using urinary tin levels measured by inductively coupled plasma mass spectrometry (ICP-MS). Urinary tin levels are associated with chronic health outcomes, such as diabetes; however, it is unclear if these associations are due to the presence of inorganic and organic forms of tin in urine. To address this knowledge gap, levels of total tin and several organotin compounds (OTCs) were measured in convenience urine samples from pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…However, in a small cohort (55 individuals) of Danish women, significant levels of TBT were not identified in a study conducted by the National Toxicology Program (NTP) [391]. Significantly, it was recently shown that plastic specimen containers of the type universally used in such studies were strong binders of TBT and other organotins, markedly reducing organotin recovery during analysis [392]. Therefore, previous studies of organotin levels in human specimens, including the NTP study, probably substantially underestimated TBT levels because they used plastic blood and specimen containers during processing and analysis.…”
Section: Human Studiesmentioning
confidence: 99%
“…However, in a small cohort (55 individuals) of Danish women, significant levels of TBT were not identified in a study conducted by the National Toxicology Program (NTP) [391]. Significantly, it was recently shown that plastic specimen containers of the type universally used in such studies were strong binders of TBT and other organotins, markedly reducing organotin recovery during analysis [392]. Therefore, previous studies of organotin levels in human specimens, including the NTP study, probably substantially underestimated TBT levels because they used plastic blood and specimen containers during processing and analysis.…”
Section: Human Studiesmentioning
confidence: 99%
“…The health impacts of Sn are less explored than those of Pb despite Sn's environmental prevalence. No safe exposure level for Sn has been established, with its inorganic forms known to inhibit the absorption of essential minerals like iron, zinc, and calcium due to inefficient absorption and fast excretion [ 113 ]. Acute exposure to Sn can cause gastrointestinal distress, such as nausea [ 114 ], and long-term exposure is associated with an increased risk of diabetes and obesity [ 115 ].…”
Section: Pscs Potential Impact On Human Healthmentioning
confidence: 99%
“…Acute exposure to Sn can cause gastrointestinal distress, such as nausea [ 114 ], and long-term exposure is associated with an increased risk of diabetes and obesity [ 115 ]. Sn is mainly eliminated through urine, and its toxicity varies by age and compound form, with organic Sn compounds potentially disrupting endocrine and renal functions [ 113 , 116 ].…”
Section: Pscs Potential Impact On Human Healthmentioning
confidence: 99%
“…Tributyltin, a component of marine antifouling paint, can be enriched in the human body through the food chain, posing a threat to human health. , Tributyltin pollution is an important problem in some coastal areas. Butyltin in seafood from the Polish Baltic Sea coast is as high as 1132 ng Sn/g dw . In humans, median levels of total tin and organotin compounds detected in urine samples of pregnant women and adults in Iowa, USA, were 0.20 ng/mL and 0.57 ng/mL, respectively . Tributyltin has even been detected in the placentas of newborns at an average of 0.32 ng/g fresh body weight in Finland and Denmark. , …”
Section: Introductionmentioning
confidence: 99%